Effects of psyllium therapy on stool characteristics, colon transit and anorectal function in chronic idiopathic constipation - ASHRAF, W.; PARK, F.; LOF, J.; QUIGLEY, E. M. M. (Alimentary pharmacology & therapeutics, 1995)
SUMMARY Background: Psyllium is widely used in the symptomatic therapy of constipation. Its effects on colonic function and their correlation with symptomatic response have not been defined. Methods: After a 4‐week baseline, placebo, run‐in phase, 22 subjects with idiopathic constipation confirmed by prospectively administered stool diaries were randomly assigned to receive either psyllium (5 g b.d., 11 patients) or placebo (11 patients) for 8 weeks, followed by another 4‐week wash‐out, placebo phase. A colon transit study and anorectal manometry were performed at the beginning and at the end of each study phase. Subjects recorded, in diaries, their daily stool frequency, difficulty with defecation and weekly stool weight. Results: Stool frequency increased significantly after 8 weeks of psyllium treatment (3.8 ± 0.4 vs. 2.9 ± 0.1 stools/week, P < 0.05) as did stool weight (665.3 ± 95.8 g vs. 405.2 ± 75.9 g, P < 0.05). Subjects also reported an improvement in stool consistency (stool consistency score: 3.2 ± 0.2 vs. 3.8 ± 0.2, P < 0.05) and pain on defecation (pain score: 2.0 ± 0.4 vs. 2.6. ± 0.5, P < 0.05) on psyllium. Colon transit and anorectal manometry parameters were unchanged on psyllium. Subjects treated with placebo did not show any change in either subjective or objective measures of constipation. Conclusions: Psyllium increases stool frequency and weight and improves stool consistency in idiopathic constipation. These effects are not associated with significant changes in either colonic or rectal motor function. We suggest that the beneficial effects of psyllium in constipation are primarily related to a facilitation of the defecatory process.